Microsoft Power Apps Cookbook - Mendoza, Eickhel (Packt Publishing, 2021)
Practical recipes that go beyond official documentation to help you create custom solutions, automate processes, and extend the platform's capabilities using Power Apps, Power Automate, Component Framework, and Dataverse for Teams Key Features Improve business operations by creating impactful Power Apps solutions with real-world use cases Explore a variety of built-in templates to create custom apps for specific business scenarios Strengthen your enterprise applications with advanced techniques and proven tips using a low-code approach Book Description Microsoft Power Apps provides a powerful, low-code solution for application development, empowering non-technical users to create robust, practical solutions in no time. This book will help you create a wide range of custom business solutions using the ease of development that Power Apps provides by overcoming many of the challenges faced in business application development. You'll start by getting to grips with Power Apps Studio and finding out how canvas apps help you build pixel-perfect applications as per business needs. The book then covers the practicalities involved in designing model-driven apps and teaches you how to automate business processes using Power Automate. You'll also discover how to improve user experience (UX) to make applications more appealing. As you advance, you'll learn how to strengthen your business apps by using AI Builder's artificial intelligence capabilities. You'll also explore advanced troubleshooting techniques to find creative ways to overcome various challenges in your Power Apps solutions. The book concludes with Power Apps Component Framework to help you further improve the existing applications' capabilities. By the end of this book, you'll have gained experience in developing applications using the Power Apps platform and its features. What you will learn Build pixel-perfect solutions with canvas apps Design model-driven solutions using various features of Microsoft Dataverse Automate business processes such as triggered events, status change notifications, and approval systems with Power Automate Implement AI Builder's intelligent capabilities in your solutions Improve the UX of business apps to make them more appealing Find out how to extend Microsoft Teams using Power Apps Extend your business applications' capabilities using Power Apps Component Framework Who this book is for This book is for citizen developers and business users looking to build cust...